What about cerebral venous sinus thrombosis? A series of three autopsy cases. (May 2022) - Tomassini, Luca; Paolini, Daniele; Petrasso, Pia Eugenia Ylenia; Manta, Anna Maria; Piersanti, Valeria; Straccamore, Marco; Ciallella, Costantino
Highlights: Cerebral Venous Sinus Thrombosis – a popular topic during the Sars-CoV-2 pandemic. Cerebral Venous Sinus Thrombosis as the end point of different processes – a case series. The study of dura mater and venous sinuses during autopsy – the role of the forensic pathologist. Cerebral Venous Sinus Thrombosis in medical malpractice. Abstract: Cerebral venous sinus thrombosis (CVST) is an uncommon cerebrovascular disorder that gained massive media attention in 2021, when an association between COVID-19 and its vaccines was found in several reported cases, raising the suspicion of a causative relation that is still debated. Three cases of CVST unrelated to COVID-19 are reported in this article to highlight the difficulty in the early recognition and management of this condition, as it occurs in a variety of diseases with different clinical and pathological manifestations. When the diagnosis cannot be achieved in the clinical setting, the role of the pathologist becomes essential in the determination of the cause of death and in the identification of the etiology of CVST. During the autopsy, coordination between the physician and the forensic pathologist is crucial to correlate the clinical presentation with the pathological picture.